ANALISIS MANAJEMEN USAHATANI JERUK SIAM DI DESA LIMAU MANIS KECAMATAN KAMPAR KABUPATEN KAMPAR - Afri ' Firman; Evy Maharani ' Maharani; Jum’atri ' Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research is the aim to know (1) the implementation of the functions of the management of orange usahatani siam in the village Limau Manis Kampar District Kampar Regency, and (2) The problems faced in the management of usahatani oranges. The location of the selected research deliberately (purposive). The Data used consists of primary data and secondary data. The method used for this study is the analysis of qualitative description ( Deskriptive Metodh Qualitative) namely explain in detail about the implementation of the functions of the management of orange usahatani siam. The results of the study showed the management usahatani oranges siam in the village of lime Sweet is in accordance with the functions of management, visible from the functions of management applied by the farmers to businesses tani oranges siam in havent then. The problems faced by the farmers oranges siam in the village of lime sweet a little land problems, fluctuations in the price of which is uncertain, pembiayaaan usahatani still less and the implementation of technology that is still low. Key Words : Management Function, Problem Oranges Siam, qualitative description.